Idiosyncratic Shocks and Aggregate Fluctuations in an Emerging Market - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2021)
This paper provides the first assessment of the contribution of idiosyncratic shocks to aggregate fluctuations in an emerging market using confidential data on the universe of Chilean firms. We find that idiosyncratic shocks account for more than 40 percent of the volatility of aggregate sales. Although quite large, this contribution is smaller than documented in previous studies based on advanced economies, despite a higher degree of market concentration in Chile.We show that this finding is explained by larger firms being less volatile and by weaker propagation effects across Chilean firms.